Influence of Marketing MIX 4P (Product, Price, Place, Promotion) On Purchase Decision at PT. Alfa Scorpii Setia Budi Branch Medan - Fitri Anjelika; Triana Melinda Sinaga (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of product, price, promotion and place on purchase decision at PT. Alfa Scorpii Setia Budi Medan. This type of research is explanatory research. The population in this study were all consumers of PT. Alfa Scorpii Setia Budi branch totaling 517 consumers. The technique for determining the sample is using the Slovin formula for an error tolerance level of 10% so that 84 samples are obtained. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that product, price, promotion and place partially or simultaneously have a positive and significant effect on consumer purchase decision at PT. Alfa Scorpii Setia Budi Medan. Based on the results of this study, the implications for management are to further improve quality for each product, determine a better price, update the promotion to make it look attractive and provide even more attractive places.